2015
DOI: 10.17219/dmp/59498
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear Bond Strength of the Composite to Biodentine with Different Adhesive Systems

Abstract: A -koncepcja i projekt badania, B -gromadzenie i/lub zestawianie danych, C -analiza i interpretacja danych, D -napisanie artykułu, E -krytyczne zrecenzowanie artykułu, F -zatwierdzenie ostatecznej wersji artykułu StreszczenieWprowadzenie. Materiał Biodentine, o właściwościach mechanicznych zbliżonych do zdrowej zębiny, znalazł szerokie zastosowanie w stomatologii zachowawczej i endodoncji. Zasadnicze znaczenie dla trwałości odbudowy warstwowej ma wytrzymałość połączenia między Biodentine i materiałem kompozyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The tests were carried out 12 min and 24 h after the preparation of the Biodentine material. 10 The high est bond strength (19.56 MPa) was found in the 2stage SE system after 24 h. According to our study, the highest [MPa], broken down by the type of the adhesive system and the number of layers of the adhesive system vs the control system bond strength (5.92 MPa) was also noted for the SE sys tem, but used in the 1stage strategy, with the application time of 30 s. Odabaş et al reported that the lowest values were recorded in the group where the TE system was used after 12 min, 10 which was confirmed by our earlier study 18 and the present one. Hashem et al pointed out that the choice of the adhesive strategy is not that important for improving the reliability of the bond strength of a resin composite to Biodentine.…”
Section: Discussionsupporting
confidence: 74%
“…The tests were carried out 12 min and 24 h after the preparation of the Biodentine material. 10 The high est bond strength (19.56 MPa) was found in the 2stage SE system after 24 h. According to our study, the highest [MPa], broken down by the type of the adhesive system and the number of layers of the adhesive system vs the control system bond strength (5.92 MPa) was also noted for the SE sys tem, but used in the 1stage strategy, with the application time of 30 s. Odabaş et al reported that the lowest values were recorded in the group where the TE system was used after 12 min, 10 which was confirmed by our earlier study 18 and the present one. Hashem et al pointed out that the choice of the adhesive strategy is not that important for improving the reliability of the bond strength of a resin composite to Biodentine.…”
Section: Discussionsupporting
confidence: 74%
“…The carbon spacer influences monomer flexibility, solubility, wetting, and the hydrophobicity-hydrophilicity balance [46]. This additional chemical interaction between MDP and dentin is thought to be responsible for the substantial improvement in bond durability [24,47,48]. This may also be the reason that Single Bond Universal had the highest mean SBS compared to all other adhesives used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…MTA, using a layer of reinforced glass ionomer (Riva self-cure, SDI limited, Bayswater, Victoria, Australia) followed by resin composite (Filtek z250 universal restorative, 3 obtain PRP without erythrocytes and leukocytes. PRF: 10 mL blood was collected in a sterile tube without anticoagulant and centrifuged immediately for 10 min at a speed of 3000 rpm (Andreas Hettich Group, Ltd., Tuttlingen, Germany).…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…CH used as a root-canal dressing, aside from involving time-absorbing treatment, was found to increase the risk of root fracture [ 1 ], whereas apical MTA plugs seem to be more effective, although expensive and difficult to handle [ 2 ]. An alternative, calcium silicate-based material, Biodentine, showed promising results, however, its immediate bonding to composite resin restoration may be impaired [ 3 ]. Unfortunately, apexification independent of the material used to produce the apical barrier does not allow for the revitalization and further root development of the immature, necrotic tooth [ 4 ], thereby compromising its prognosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%